A harmless evil: Giant fungating benign breast mass in an adolescent mimicking malignancy - Case report. (March 2021) - Heng, Sophia Si Ling; Yahya, Maya Mazuwin; Sulaiman, Wan Azman Wan; Saad, Arman Zaharil Mat
Highlights: Fungating, ulcerating giant fibroadenomas in adolescents are rare. When breast conserving methods are impossible, breast reconstruction should be the focus. Management of these cases should be tailored to each patient. Awareness on negative effects of traditional medicine should be raised. Abstract: Introduction: Juvenile giant fibroadenoma is a rare type of fibroadenoma characterized by rapid growth of a breast tumor in an adolescent. Benign in nature, they rarely present as fungating and ulcerating tumors. Benign tumors masquerading as malignancies are surgical conundrums. No co nsensus exists yet on the management of these cases. We aim to discuss the dilemma in managing a bleeding, fungating giant fibroadenoma in an adolescent female and highlight risks of alternative therapies. Presentation of case: A 19-year-old lady presented with a bleeding, fungating breast mass worsened with topical herbal concoction. Examination revealed a 10 × 15 cm fungating breast mass that obliterated her nipple- areolar complex (NAC). Computed Tomography (CT) scan reported a huge heterogeneously enhancing mass 10.6 × 14.5 × 15.1 cm with loss of normal fat plane with the overlying skin but a clear fat plane with the pectoralis muscle posteriorly. Discussion: Giant breast masses that fungate and ulcerate usually indicate a sinister pathology. Traditional remedies have been reported to exacerbate growth. In cases where most of the breast parenchyma and NAC has been destroyed, it is no longer possible to proceed with breast conserving techniques. Breast reconstruction is crucial in adolescents and should be tailored to the patient's existing breast size as well as body habitus. Conclusion: In juvenile giant fibroadenomas where breast parenchyma and NAC has been destroyed, breast reconstruction is the goal. The lack of consensus in both diagnosis and management further compounds the difficulty in dealing with this sensitive population. Awareness needs to be raised regarding negative effects related to traditional medicine.